An Eulerian-Lagrangian snow drifting model for gable roofs considering the effect of roof slope. Issue 234 (March 2023) - Zhou, Xuanyi; Zhang, Tiange; Liu, Zhenbiao; Gu, Ming
Abstract: Roof slopes would have a great impact on snow drifting on roofs. The existing Eulerian-Lagrangian model is not suitable for simulations of snow drifting on gable roofs. This study improves the Eulerian-Lagrangian snow drifting model by modifying the threshold friction velocity and the splash functions to fully consider the impact of the roof slope. To evaluate the rationality of the improved model, scaled tests of snow redistributions on gable roofs were conducted in a wind tunnel. The improved model is demonstrated to perform better on the prediction of snow redistributions on gable roofs. Characteristics of snow drifting on gable roofs with different slopes are investigated in terms of flow pattern, particle motion and snow transport. For roofs with different slopes, features of particle motion near the snow bed show significant differences, which are reflected in the spatial distribution, the saltation height and the impact velocity of snow particles. Snow erosion occurs on the windward roof at each slope, and it also occurs on the leeward side at the slope of 5° or 10°. However, on the entire leeward surface at the slope of 15° and near the ridge at the slope of 20°, snow deposition would occur. Highlights: An Eulerian-Lagrangian snow drifting model for gable roofs considering the effect of roof slope is established. Scaled wind tunnel tests of snow redistributions on gable roofs were conducted to evaluate the rationality of the model. Features of particle motion close to the roof surface are revealed through the analyses of the simulated results. Characteristics of snow erosion/deposition flux and snow transport rate on gable roofs are discussed.